Analisis Isi Terhadap Potret Kehidupan Santri di Pesantren Dalam Akun Instagram “Alasantri” - Putri, Fitri Ariana (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2022)
The pattern applied in life in Islamic boarding schools to encourage students to be more independent both in fulfilling their living needs, tidying themselves up, tidying up the surrounding environment and learning independence. with the five souls of Islamic boarding schools, namely the soul of sincerity, the soul of simplicity, the soul of independence, the soul of Islamic Brotherhood and the soul of freedom. In Islamic boarding schools as educational institutions or as a place to learn both formally and non-formally to provide knowledge by educating, teaching with the rules in Islamic boarding schools to form a character that is akhlaqul karimah. The purpose of this study was to determine the portrait of the life of students in Islamic boarding schools in the Instagram account "Alasantri". The method in this study used qualitative research with a content analysis approach according to Krippendorf. And the results of this finding which describes the portrait of the life of students in Islamic boarding schools that are in accordance with the five souls of the boarding school as many as nine posts including lalaran, togetherness "Alasantri" by singing, muhadhoroh, wallet "Alasantri" appearance of students, majority of students, manners above knowledge and Islamic boarding school facilities.